2016
DOI: 10.4172/2472-1220.1000114
|View full text |Cite
|
Sign up to set email alerts
|

Cold Storage Exacerbates Renal and Mitochondrial Dysfunction Following Transplantation

Abstract: Long-term renal function is compromised in patients receiving deceased donor kidneys which require cold storage exposure prior to transplantation. It is well established that extended cold storage induces renal damage and several labs, including our own, have demonstrated renal mitochondrial damage after cold storage alone. However, to our knowledge, few studies have assessed renal and mitochondrial function after transplantation of rat kidneys exposed to short-term (4 hr) cold storage compared to transplant w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
20
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(21 citation statements)
references
References 23 publications
1
20
0
Order By: Relevance
“…Figure 6A shows a bottom-up proteomic analysis of latently infected kidney allografts at 3 hours, 24 hours, and 48 hours. Oxidative phosphorylation and mitochondrial dysfunction, typically activated pathways associated with transplant IRI, 3436 such as cellular stress responses, including the DNA damage response, mitochondrial stress, and oxidative responses, were all activated after transplant compared with controls in both mice treated with IS or without IS. Figure 6B shows a protein analysis on plasma obtained from kidney recipients of latently infected allografts 48 hours posttransplant.…”
Section: Resultsmentioning
confidence: 96%
“…Figure 6A shows a bottom-up proteomic analysis of latently infected kidney allografts at 3 hours, 24 hours, and 48 hours. Oxidative phosphorylation and mitochondrial dysfunction, typically activated pathways associated with transplant IRI, 3436 such as cellular stress responses, including the DNA damage response, mitochondrial stress, and oxidative responses, were all activated after transplant compared with controls in both mice treated with IS or without IS. Figure 6B shows a protein analysis on plasma obtained from kidney recipients of latently infected allografts 48 hours posttransplant.…”
Section: Resultsmentioning
confidence: 96%
“…Indeed, aberrant complement activation is detected during acute and chronic allograft rejection in humans, but the direct connection between cold ischemia (during CS) and complement activation in renal graft is not clear. Here, we demonstrate, for the first time, that CS induces abnormal complement activity in rat renal transplants compared with ATx (no CS exposure), which correlates with graft dysfunction (26,27). This is the first study in an animal model, if any, to perform head-tohead comparisons in transplants with or without CS (but similar warm ischemia time during the transplant process), and these results highlight why prolonged CS produces unfavorable outcomes in the grafts after transplantation.…”
Section: Discussionmentioning
confidence: 57%
“…Our recent work with rat transplant models indicated that CS exacerbates renal damage and dysfunction in transplanted kidneys (compared with no CS) (25)(26)(27). We further demonstrated that proteasome function is decreased, protein homeostasis is altered, and albumin is modified within kidneys after CS plus transplantation (25,28).…”
Section: Introductionmentioning
confidence: 68%
“…Given that prolonged CS followed by warm IRI produces ROS [37,39], and that ROS modulate the constitutive proteasome function [144][145][146], we can postulate that CS/Tx-mediated ROS could trigger denaturation of intracellular proteins and modulation of the constitutive proteasome function. Indeed, a recent report demonstrated that the chymotrypsin-like activity of the proteasome was compromised after renal CS/Tx [147], and that this correlated with severe renal dysfunction [80,90]. A study performed by using pharmacological inhibition of chymotrypsin-like activity of the proteasome during warm IRI showed aggravated renal damage [148].…”
Section: The Proteasomementioning
confidence: 99%
“…Studies further suggest that more severe mitochondrial respiratory dysfunction occurs after CS/Tx (cold ischemia + warm IRI) than transplantation without CS (only warm IRI) and further revealed that CS/Tx decreases the function of mitochondrial complexes I, II, III, and V [80]. Mitochondrial respiratory dysfunction during renal CS/Tx leads to reduced levels of ATP, accumulation of ROS, and increased renal damage, suggesting that the "damage" signals from CS likely begin with alterations in mitochondrial function [37,80,[84][85][86][87][88][89][90]. Normally, mitochondrial ROS are primarily detoxified by manganese superoxide dismutase (MnSOD), a mitochondrial antioxidant enzyme.…”
Section: Mitochondrial Respiratory Complex and Rosmentioning
confidence: 99%